Eicosapentaenoic Acid, Arachidonic Acid and Eicosanoid Metabolism in Juvenile Barramundi Lates calcarifer. Issue 8 (14th June 2016) - Salini, Michael J.; Wade, Nicholas M.; Araújo, Bruno C.; Turchini, Giovanni M.; Glencross, Brett D.
Abstract: A two part experiment was conducted to assess the response of barramundi ( Lates calcarifer ; initial weight = 10.3 ± 0.03 g; mean ± S.D.) fed one of five diets with varying eicosapentaenoic acid (diets 1, 5, 10, 15 and 20 g/kg) or one of four diets with varying arachidonic acid (1, 6, 12, 18 g/kg) against a fish oil control diet. After 6 weeks of feeding, the addition of EPA or ARA did not impact on growth performance or feed utilisation. Analysis of the whole body fatty acids showed that these reflected those of the diets. The ARA retention demonstrated an inversely related curvilinear response to either EPA or ARA. The calculated marginal utilisation efficiencies of EPA and ARA were high (62.1 and 91.9 % respectively) and a dietary ARA requirement was defined (0.012 g/kg 0.796 /day). The partial cDNA sequences of genes regulating eicosanoid biosynthesis were identified in barramundi tissues, namely cyclooxygenase 1 ( Lc COX1a, Lc COX1b ), cyclooxygenase 2 ( Lc COX2 ) and lipoxygenase ( Lc ALOX ‐ 5 ). Both Lc COX2 and Lc ALOX ‐ 5 expression in the liver tissue were elevated in response to increasing dietary ARA, meanwhile expression levels of Lc COX2 and the mitochondrial fatty acid oxidation gene carnitine palmitoyltransferase 1 ( Lc CPT1a ) were elevated in the kidney. A low level of EPA increased the expression of Lc COX1b in the liver. Consideration should be given to the EPA to ARA balance for juvenile barramundi in light of nutritionally inducible nature of the cyclooxygenase and lipoxygenase enzymes.